2002
DOI: 10.1093/emboj/cdf302
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin requires Brg-1 and Brm for the repression of E2F and cell growth

Abstract: E2F transcription factors play a major role in controlling mammalian cell cycle progression. We recently reported that a potential tumor suppressor, prohibitin, which interacts with retinoblastoma protein (Rb), regulates E2F function and this activity correlates with its growth-suppressive activity. We show here that prohibitin recruits Brg-1/Brm to E2F-responsive promoters, and that this recruitment is required for the repression of E2F-mediated transcription by prohibitin. Expression of a dominantnegative Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
1
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(156 citation statements)
references
References 32 publications
4
146
1
5
Order By: Relevance
“…Using anti-prohibitin antibodies, we initially immunoprecipitated chromatin from HEK293 cells and performed ChIP PCR with E2F1, TK and p107 primers, which were previously reported to be prohibitin-recruiting promoters (Wang et al, 2002). As expected, prohibitin was recruited to the promoters Interaction between prohibitin and RNF2 D Choi et al tested (Figure 7d, left panel).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Using anti-prohibitin antibodies, we initially immunoprecipitated chromatin from HEK293 cells and performed ChIP PCR with E2F1, TK and p107 primers, which were previously reported to be prohibitin-recruiting promoters (Wang et al, 2002). As expected, prohibitin was recruited to the promoters Interaction between prohibitin and RNF2 D Choi et al tested (Figure 7d, left panel).…”
Section: Resultsmentioning
confidence: 60%
“…Prohibitin represses the transcriptional activity of E2Fs1-5 by recruiting co-repressors, including histone deacetylase 1, N-CoR and BrG1/ Brm (Wang et al, 2002), whereas Rb represses the transcriptional activity of E2Fs1-3 by recruiting histone deacetylase 1, DNA methyltransferase and BrG1/Brm (Luo et al, 1998;Magnaghi-Jaulin et al, 1998;Zhu, 2005). Prohibitin and Rb interact with distinct regions of E2F1 and respond to different upstream signals (Wang et al, 1999b).…”
Section: Introductionmentioning
confidence: 99%
“…Injection of the mRNA results in cell-cycle arrest in some cell types (McClung et al, 1989;Nuell et al, 1991), and this may in part be due to the 3 0 untranslated region (3 0 UTR) of the mRNA (Jupe et al, 1996). Even the localization of the protein is not clear, with some groups maintaining that the protein is purely mitochondrial (Coates et al, 2001), and others demonstrating a secondary localization in the nucleus (Thompson et al, 2001;Wang et al, 2002b). However, recent observations that prohibitin can interact with members of the E2F transcription factor family (Wang et al, 1999a) support the concept of a nuclear role in cell-cycle regulation.…”
Section: Introductionmentioning
confidence: 99%
“…One potential mechanism whereby PHB regulates beclin-1, the first mammalian gene shown to induce autophagy, is through the transcription factor E2F1. The beclin-1 promoter contains a putative E2F1 binding site [57] and PHB has been shown to regulate E2F1 activity [35]. Future studies will investigate this possibility.…”
Section: Discussionmentioning
confidence: 98%
“…Prohibitin 1 (PHB) is an evolutionarily conserved, multifunctional 32 kDa protein implicated in cellular processes including the regulation of proliferation, apoptosis, and transcription [33,34,35,36]. PHB is predominantly localized to the mitochondria in intestinal epithelial cells [37] and multiple studies have shown that PHB plays a role in maintaining normal mitochondrial function and morphology (reviewed in [38]).…”
Section: Introductionmentioning
confidence: 99%